Kajian Green Infrastructure dalam Upaya Menambah Ketersediaan Air Tanah di Kota Bandung - Atha Retha Hanani; Hilwati Hindersah (UNISBA Press, 2022)
Abstract. Water is a natural resource that is a basic need for all living things, especially humans. Groundwater is one of the sources of water used by humans. However, the condition of groundwater in Bandung City is currently experiencing a decrease in the groundwater level caused by the use of unmeasured groundwater, while the catchment area is converted into housing. For this reason, this study aims to identify green infrastructure in increasing the availability of groundwater in the city of Bandung. In this study, there are 2 stages. The first stage is the analysis of the potential location for the application of green infrastructure using intersect analysis on arcgis. The second stage is an analysis of the ability of green infrastructure to increase groundwater availability using the SCS TR-55 method. The results showed that the location that has the potential to apply infiltration basin is 790.278 Ha, the location that has the potential to be applied to infiltration trench is 171,599 Ha and the location that has the potential to apply bioretention is 264.873 Ha. The calculation results show that the infiltration pond can absorb 61% of the peak discharge, the infiltration ditch can absorb 41% of the peak discharge and the bioretention capacity of 46% of the peak discharge. Abstrak. Air merupakan salah satu sumberdaya alam yang menjadi kebutuhan pokok bagi seluruh makhluk hidup khususnya manusia. Air tanah adalah salah satu sumber air yang digunakan oleh manusia. Namun kondisi air tanah di Kota Bandung saat ini terjadi penurunan muka air tanah yang disebabkan oleh penggunaan air tanah yang tidak terukur sedangkan daerah resapan dialihfungsikan menjadi perumahan. Untuk itu penelitian ini bertujuan mengidentifikasi green infrastructure dalam menambah ketersediaan air tanah di Kota Bandung. Dalam penelitian ini terdapat 2 tahapan. Tahap yang pertama yaitu analisis lokasi potensi penerapan green infrastructure menggunakan analisis intersect pada arcgis. Tahap kedua yaitu analisis kemampuan green infrastructure dalam menambah ketersediaan air tanah menggunakan metode SCS TR-55. Hasil penelitian menunjukan bahwa lokasi yang berpotensi diterapkan kolam resapan seluas 790,278 Ha, lokasi yang berpotensi diterapkan parit resapan seluas 171,599 Ha dan lokasi yang berpotensi diterapkan bioretensi seluas 264,873 Ha. Hasil perhitungan menunjukan kolam resapan dapat meresapkan air sebesar meresapkan air sebesar 61% dari debit puncak, parit resapan dapat meresapkan air sebesar 41% dari debit puncak dan kemampuan bioretensi dalam meresapkan air 46% dari debit puncak.